Impact of Retirement Benefit Administration on the Welfare of Retirees in State Tertiary Institutions of Adamawa State - Nigeria - Gladys Isa’AC (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the impact of retirement benefits administration on the welfare of retirees in state tertiary institutions in Adamawa State, Nigeria. The study adopted a descriptive research design and targeted retirees and officials of the Adamawa State Pension Board across five selected institutions, with a population of 205 and a sample size of 132 determined using the Krejcie and Morgan sample size table. Data were collected through structured questionnaires and analyzed using descriptive statistics. From the 132 questionnaires administered, 127 were retrieved, representing a response rate of 96.2%. The findings revealed that the retirement benefits administration system is moderately functional but characterized by significant gaps in transparency, communication, and accessibility. While some components such as contribution modalities and record management recorded average performance, critical areas like awareness of payment timelines and benefit tracking were weak. The study also identified key challenges, including inadequate funding, poor record management, bureaucratic bottlenecks, corruption, and policy inconsistencies, which collectively undermine the efficiency of the system. The study concluded that although the administrative structure exists, its operational inefficiencies significantly impair retirees’ welfare. It recommended improved transparency through digital platforms, enhanced pre-retirement education, streamlined administrative processes, and strengthened funding and accountability mechanisms to ensure effective service delivery.